ANALISIS YURIDIS TERHADAP PEMBATALAN UJIAN PENGANGKATAN NOTARIS OLEH MAHKAMAH AGUNG - CAROLINE CAROLINE (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Notaris Dr. Henry Sinaga, SH, MKn3. Dr. T. Keizerina Devi A, SH, CN, MHum Notarial Appointment test as it is stipulated in the Decree of the Minister of Law and Human Rights bring about legal uncertainty and conflict in norms in society. The prerequisite of appointing a Notary as it is stipulated in UUJN (Notarial Act) does not regulate a Notarial candidate who has to take the test organized by the Minister of Law and Human Rights. The conflict in norms is the reason for lodging material test on the Minister of Law and Human Rights No. 62/2016, Article 2, paragraph 2, letter j and No. 25/2017 on the Appointment of a Notary. The research problems are how about the consideration of the Minister of Law and Human Rights in the Test for Appointing a Notary and the Reason for Cancelling it, and the Implementation of appointing a Notary after it is cancelled.Keywords : Appointment Test, Notary, Ministerial Decree